Chitosan: A compound for drug delivery system in gastric cancer-a review - Shafabakhsh, Rana; Yousefi, Bahman; Asemi, Zatollah; Nikfar, Banafsheh; Mansournia, Mohammad Ali; Hallajzadeh, Jamal (Carbohydrate polymers, 2020)
•Gastric cancer is the fourth most common and the second main cause of cancer death.•Local recurrence, hematogenous metastasis and drug resistance remains yet resulting in treatment failure.•Chitosan is the only cationic marine polysaccharide.•Chitosan is an appropriate compound for chemo-drug delivery in gastric cancer treatment. Gastric cancer is known as the fourth most common cancer and the second main cause of cancer-related deaths. Gastric cancer has some characteristics including high incidence rates of metastasis and mortality as well as low rates of early diagnosis, radical resection and 5-year survival. Radical surgery and following chemotherapy has been done for patients with early gastric cancer leading to 90 % survival rate in 5-year after operation. Besides, in advanced stage some cases don’t have the chance of surgery as well as the risk of metastasis is high in these patients overally leading to poor prognosis. In recent years, finding a suitable drug delivery system for chemotherapeutic drugs in gastric cancer is an considerable subject for researchers. Chitosan is known as an appropriate compound for chemo-drug delivery in cancer treatment due to its high biodegradability and biocompatibility. Moreover, trans-mucosal drug delivery is facilitated by chitosan via its mucoadhesive and cationic features enhancing interaction with mucous membrane. In addition, a large amount of experimental evidence has reported the efficacy of chitosan for drug delivery in gastric cancer. Thus, the aim of this article was to review this evidence as well as new chitosan-based drug delivery systems investigated in gastric cancer.